Match-Play and Performance Test Responses of Soccer Goalkeepers: A Review of Current Literature - Liam Kilduff (Sports Medicine, 2018)
Goalkeepers are typically the last defensive line for soccer teams aiming to minimise goals being conceded, with match rules permitting ball handling within a specific area. Goalkeepers are also involved in initiating some offensive plays, and typically remain in close proximity to the goal line while covering ~ 50% of the match distances of outfield players; hence, the competitive and training demands of goalkeepers are unique to their specialised position. Indeed, isolated performance tests differentiate goalkeepers from outfield players in multiple variables. With a view to informing future research, this review summarised currently available literature reporting goalkeeper responses to: (1) match play (movement and skilled/technical demands) and (2) isolated performance assessments (strength, power, speed, aerobic capacity, joint range of motion). Literature searching and screening processes yielded 26 eligible records and highlighted that goalkeepers covered ~ 4–6 km on match day whilst spending ~ 98% of time at low-movement intensities. The most decisive moments are the 2–10 saves·match−1 performed, which often involve explosive actions (e.g. dives, jumps). Whilst no between-half performance decrements have been observed in professional goalkeepers, possible transient changes over shorter match epochs remain unclear. Isolated performance tests confirm divergent profiles between goalkeepers and outfield players (i.e. superior jump performance, reduced \({\dot{\text{V}}\text{O}}\)2max values, slower sprint times), and the training of soccer goalkeepers is typically completed separately from outfield positions with a focus primarily on technical or explosive drills performed within confined spaces. Additional work is needed to examine the physiological responses to goalkeeper-specific training and match activities to determine the efficacy of current preparatory strategies.